Resistance of Chitti bean genotypes of promising to two-spotted spider mite Tetranychus urticae Koch in greenhouse conditions - Sedigheh Ashtari; Behrouz Asadi; Hamid Reza Dorri (نامه انجمن حشره‌شناسی ایران)
Tetranychus urticae Koch (Acari: Tetranychidae), The two-spotted spider mite (TSSM), is one of the most significant pests infesting beans and a large amount of insecticides are used annually against it. The present research was conducted to identify resistance levels of chitti bean genotypes to ward T. urticae. For the experiments, Type 1 bean genotypes (standing) (KS-21216, KS-21181, KS-21538, KS-21565, KS-21563, KS-21602, KS-21500, KS-21601, KS-21600, and KS-21607), Type 2 genotypes (half standing) (KS-21573, KS-21597, and KS-21606), and Type 3 genotypes (prostrate) (KS-21255 and KS-21574), along with the susceptible variety (Sadri), were cultivated in the field at the Khomein National Bean Research Station in a randomized complete block design with three replications during two successive years (2022 and 2023). To examine the population (egg, nymph, larval and adult stages), ten plants were randomly selected from each plot, and from each plant, two heaves from the top, two from the middle, and two from the bottom of the canopy, were selected. The sampling program was conducted weekly from the third leaf stage until the end of the season. The resistance mechanism (not from the biochemical aspects) was determined (tolerance, antixenosis and antibiosis) under greenhouse conditions on the same varieties. The results of population changes revealed the highest number of eggs, nymphs, larvae, and adults of T. urticae were observed in the Sadri variety and genotype KS-21607. In contrast, the lowest was ascertained in genotypes KS-21216, and KS-21184. According to greenhouse results Sadri variety and genotype KS-21607 were classified as susceptible to TSSM with damage scales of 5.90±0.10 and 4.80±0.12 respectively. Genotypes KS-21538, KS-21216, KS-21184, and KS-21255 exhibited desirable antibiosis-type resistance mechanisms. But, the Sadri variety and genotypes KS-21607, KS-21573 and KS-21597, supported a high reproductive and growth fitness of T. urticae.